2017
DOI: 10.1016/j.psychres.2017.06.036
|View full text |Cite
|
Sign up to set email alerts
|

Polyunsaturated fatty acid composition and childhood adversity: Independent correlates of depressive symptom persistence

Abstract: Childhood experiences, personality, and polyunsaturated essential fatty acid (PUFA) composition have all been shown to affect the likelihood of depressive symptoms. Few studies have addressed relationships between these factors in their influence on the occurrence or course of depressive symptoms. The following analysis was designed to do so. Subjects, 15 to 20 years old, had either begun antidepressant treatment within the preceding month (n=88), or had never taken psychiatric medications (n=92). Baseline ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 64 publications
0
5
0
Order By: Relevance
“…Peng et al found that mental disorders were associated with higher CTQ scores and lower SSRS scores ( 34 ). Childhood experiences, characters, and childhood trauma have all been shown to correlate with the occurrence of anxiety and depressive disorder ( 61 ). Moreover, childhood trauma would increase the persistence of comorbidity and chronic disease in patients with anxiety and/or depressive disorders ( 62 ) and contribute to the severity of psychopathology ( 63 , 64 ).…”
Section: Discussionmentioning
confidence: 99%
“…Peng et al found that mental disorders were associated with higher CTQ scores and lower SSRS scores ( 34 ). Childhood experiences, characters, and childhood trauma have all been shown to correlate with the occurrence of anxiety and depressive disorder ( 61 ). Moreover, childhood trauma would increase the persistence of comorbidity and chronic disease in patients with anxiety and/or depressive disorders ( 62 ) and contribute to the severity of psychopathology ( 63 , 64 ).…”
Section: Discussionmentioning
confidence: 99%
“…In rats, it was demonstrated that a maternal separation paradigm induced a shift in the plasma PUFAs towards a more pro-inflammatory profile, with an increased concentration of AA in the maternally separated group [ 33 ]. In humans, previous work has investigated the relationship between plasma PUFA levels in young adults, early life trauma, and depressive symptoms, which revealed that low omega-3 FA levels and a history of trauma are both associated with persistence of depressive symptoms, but not correlated to each other [ 34 ]. However, plasma and brain FA levels do not appear to be correlated [ 35 ], emphasizing the importance of human postmortem brain tissue with well-documented histories of maltreatment for obtaining a comprehensive picture of lipid-related changes associated with early-life adversity.…”
Section: Discussionmentioning
confidence: 99%
“…ELOVL2 is responsible for the elongation of omega n-3 (anti-inflammatory; first unsaturated bond at the third carbon relative to the terminal methyl end) and omega n-6 (pro-inflammatory; first unsaturated bond at the sixth carbon) PUFAs (Bandeira-Melo, Bozza, & Weller, 2002; Bozza & Bandeira-Melo, 2005; Schmitz & Ecker, 2008) in the liver. An ELOVL2-mediated dysregulation of n-3 and n-6 PUFAs metabolism could explain the link between CM experiences and the observed higher risk for conditions related to fatty acid metabolism such as obesity (Hemmingsson, Johansson, & Reynisdottir, 2014), diabetes (Basu, McLaughlin, Misra, & Koenen, 2017; Huang et al, 2015), and cardiovascular outcomes (Basu et al, 2017), and could increase the risk for Alzheimer's disease (Snowden et al, 2017) and major depression (Coryell et al, 2017; Kiecolt-Glaser et al, 2007). Thus, the higher methylation of exon 1 ELOVL2 observed with increasing CM severity might be part of a pathway towards adult physical and psychological pathology in combination with other environmental factors.…”
Section: Discussionmentioning
confidence: 99%